MafA Regulation in β-Cells: From Transcriptional to Post-Translational Mechanisms - Jiani Liang; Margot Chirikjian; Utpal B. Pajvani; Alberto Bartolomé (Biomolecules, 2022)
β-cells are insulin-producing cells in the pancreas that maintain euglycemic conditions. Pancreatic β-cell maturity and function are regulated by a variety of transcription factors that enable the adequate expression of the cellular machinery involved in nutrient sensing and commensurate insulin secretion. One of the key factors in this regulation is MAF bZIP transcription factor A (MafA). MafA expression is decreased in type 2 diabetes, contributing to β-cell dysfunction and disease progression. The molecular biology underlying MafA is complex, with numerous transcriptional and post-translational regulatory nodes. Understanding these complexities may uncover potential therapeutic targets to ameliorate β-cell dysfunction. This article will summarize the role of MafA in normal β-cell function and disease, with a special focus on known transcriptional and post-translational regulators of MafA expression